Multi-agent systems as automation platform for intelligent energy systems - Leitão, Paulo (2014)
The large-scale integration of distributed energy resources into a complex cyber-physical system demands proper automation platforms for monitoring, control, optimization and reconfiguration, addressing intelligent energy systems. This paper discusses the use of multi-agent systems as a suitable solution to address this challenge by analyzing their benefits when applying them to the field of Smart Grids and surveying existing works and initiatives. The principles and use cases established in the MASGrid project illustrate the application of multi-agent technology in active power distribution systems.